JUSTICE IN THE MAQASHID APPROACH AL-SYARI'AH - Ananda, Faisar; Nurasiyah, Nurasiyah; Nasution, Muhammad Hasan (Al-Usrah : Jurnal Al Ahwal As Syakhsiyah, 2024)
This article describes the concept of justice from the perspective of Islamic legal philosophy. There are two main formulations of justice in this context: The first view considers justice as a harmony between rights and obligations, which is based on the postulate of "legal balance" or "measure of rights and obligations". In this view, every individual has rights and obligations that are both balanced and mutually supportive. The second view states that justice is a harmony between legal certainty and legal comparability. In this case, justice is achieved when the law is enforced with certainty and fairness, so that there is no discrimination or inequality in its application